'Alert not alarm': The UK experience of public counter-terrorism awareness and training, with explicit reference to Project ARGUS. (September 2020) - Aplin, Dylan; Rogers, Marian Brooke
This study evaluates the contribution of a UK counter-terrorism training tool, the Project ARGUS simulation exercise format, designed to increase preparedness by 'alerting not alarming' the populace to the prevailing 'severe' international terrorist threat. The paper draws upon the theoretical basis for preparedness in order to contend that, despite exceeding expectations in terms of quantity of events delivered and evidence of immediate post-event learning, Project ARGUS does not wholly live up to its promise to change the behaviour of individuals and organisations by embedding long-term learning. The researchers designed and analysed pre- and post-event questionnaires (N = 120) in order to explore the impact of attendance at an ARGUS Retail event within a shopping centre. This information was then augmented with a follow-up survey (N = 44) and semi-structured interviews (N = 9) of key facilitators and participants. The authors recommend the immediate adoption of an appropriate evaluation and certification scheme to mandate participation and embed organisational learning. They argue that adoption of these approaches would better enable ARGUS to fulfil its potential and make a significant contribution to improving the resilience of busy crowded places to terrorism in the UK.